BARRIER TO PARENTS-ADOLESCENT COMMUNICATION ON SEXUAL AND REPRODUCTIVE HEALTH TO PREVENT PREMARITAL SEXUAL BEHAVIOUR: A QUALITATIVE SISTEMATIC REVIEW - Putri Eka Sejati; Riza Tsalatsatul Mufida; Anggrawati Wulandari (Universitas STRADA Indonesia, 2024)
Adolescence is a crucial period that will be faced with several problems, one of which is sexuality, namely premarital sex which can affect adolescent pregnancy, sexually transmitted infections, HIV and abortion. Adolescents need information about their sexual health primarily from their parents. Previous studies have shown that some sexual problems in adolescents are caused by communication failures between parents and adolescents regarding condom use, puberty, SITs, physical development, etc.This study used A Qualitative systematic review on 6 qualitative articles between 2017 to 2021, Heading Sex Education